2017
DOI: 10.5230/jgc.2017.17.e16
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factor Analysis of Overall Survival in Gastric Cancer from Two Phase III Studies of Second-line Ramucirumab (REGARD and RAINBOW) Using Pooled Patient Data

Abstract: PurposeTo identify baseline prognostic factors for survival in patients with disease progression, during or after chemotherapy for the treatment of advanced gastric or gastroesophageal junction (GEJ) cancer.Materials and MethodsWe pooled data from patients randomized between 2009 and 2012 in 2 phase III, global double-blind studies of ramucirumab for the treatment of advanced gastric or GEJ adenocarcinoma following disease progression on first-line platinum- and/or fluoropyrimidine-containing therapy (REGARD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 26 publications
(53 reference statements)
2
79
0
3
Order By: Relevance
“…Based on the dose‐escalation of Nab‐PTX with divided doses in combination with standard S‐1, in the present study, we use the recommended dose for Nab‐PTX 120 mg/m 2 on d1 and d8, q3w, achieving an efficacy/toxicity balance. A previous study showed the peritoneal metastases are an independent prognostic factor of poor survival in AGC patients . In this one‐arm trial where all patients received the same regimen, we found patients with peritoneal metastases had no significantly different efficacy or prognosis than other patients, which may indicate S‐1 plus Nab‐PTX had similar efficacy in patients with peritoneal metastases or without.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Based on the dose‐escalation of Nab‐PTX with divided doses in combination with standard S‐1, in the present study, we use the recommended dose for Nab‐PTX 120 mg/m 2 on d1 and d8, q3w, achieving an efficacy/toxicity balance. A previous study showed the peritoneal metastases are an independent prognostic factor of poor survival in AGC patients . In this one‐arm trial where all patients received the same regimen, we found patients with peritoneal metastases had no significantly different efficacy or prognosis than other patients, which may indicate S‐1 plus Nab‐PTX had similar efficacy in patients with peritoneal metastases or without.…”
Section: Discussionmentioning
confidence: 48%
“…A previous study showed the peritoneal metastases are an independent prognostic factor of poor survival in AGC patients. 28 In this one-arm trial where all patients received the same regimen, we found patients with peritoneal metastases had no significantly different efficacy or prognosis than other patients, which may indicate S-1 plus Nab-PTX had similar efficacy in patients with peritoneal metastases or without. Because the sample sizes of the subgroups in our study were small, further study is required to confirm this good observation for patients with peritoneal metastases.…”
Section: Discussionmentioning
confidence: 65%
“…As for the relationship between prognosis and histologic type, survival time was considerably shorter in patients with a diffuse histologic type according to the Lauren classification, although the difference was not statistically significant in our study. Since previous studies enrolling more than 1,000 cases showed that poor tumor differentiation was associated with a poor prognosis, the result of our study may be attributed to the relatively small number of cases enrolled [18, 24]. …”
Section: Discussionmentioning
confidence: 50%
“…A Russian group reported that PS 2, Hb < 10 g/dL, and TTP in first-line chemotherapy < 5 months were associated with a poor prognosis [22]. Recently, Fuchs et al [24], in their prognostic factor analysis based on two phase III trials of second-line ramucirumab (REGARD and RAINBOW) using pooled data, reported twelve negative prognostic factors: peritoneal metastasis, PS1, the presence of a primary tumor, TTP < 6 months after prior therapy, poor/unknown tumor differentiation, a low level of Alb, sodium, and lymphocytes, and a high level of neutrophils, aspartate aminotransferase, ALP, and lactate dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation